Preparation and application of YAG (yttrium aluminum garnet) ceramic slurry for photocuring molding

By preparing surface modified YAG powder and preparing photocuring resin, combined with ball milling and alternating electric field treatment technology, the problems of complex preparation of YAG ceramic materials and easy settlement of slurries are solved, and the efficient preparation of YAG ceramic materials with complex structures is achieved, with high stability and high mechanical properties.

CN119683990AActive Publication Date: 2025-03-25SICHUAN POLICE COLLEGE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411926012.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing YAG ceramic materials are complex in preparation process, resulting in material waste and increased costs, making it impossible to prepare devices with complex structures and fine structures. At the same time, the ceramic slurry is prone to settlement and viscosity increase, making it difficult to ensure the uniformity and mechanical properties of the print parts.

Method used

By preparing surface modified YAG powder and preparing photocuring resin, combined with ball milling and alternating electric field treatment technology, YAG ceramic slurry with high stability and suitable viscosity was prepared. The method includes mixing the YAG powder with a modifier, ball milling and drying, then mixing with a photocuring resin system, forming a preset structure by photocuring 3D printing, and finally degreasing and sintering.

Benefits of technology

The efficient preparation of YAG ceramic materials is achieved, the problems of material waste and complex structure preparation are solved, the stability and solid content of the slurry are improved, the uniformity and high mechanical properties of the prints are ensured, and the relative density reaches 97.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683990A_ABST
    Figure CN119683990A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of YAG (yttrium aluminum garnet) ceramic slurry for photocuring molding. The preparation comprises the following steps: preparing surface modified YAG powder; the preparation method comprises the following steps: preparing light-cured resin, sequentially adding a photoinitiator and a dispersant into the light-cured resin, and stirring under a dark condition to obtain a light-cured resin system mixed solution; the surface modified YAG powder and the light-cured resin system mixed solution are mixed and subjected to ball milling, and YAG ceramic slurry for light-cured forming is obtained; the YAG ceramic slurry is used for preparing a YAG ceramic material with a preset structure through photocuring 3D printing. The dispersity of the YAG powder and the stability of the slurry are improved through surface modification, the rheological property of the slurry is effectively controlled by adjusting different proportions of the light-cured resin, the photoinitiator and the dispersing agent, the requirements of light-cured forming under different conditions are met, and the relative density of the degreased and sintered YAG ceramic material reaches 97.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocuring 3D printing, and more specifically, the present invention relates to the preparation and application of a YAG ceramic slurry for photocuring molding. Background Art

[0002] Yttrium aluminum garnet (YAG) ceramics have good transmittance to visible light and infrared light, and have the advantages of high temperature resistance, high hardness, and wear resistance. It is a new type of laser material with great potential and value. Traditional YAG ceramics are mainly prepared by cold isostatic pressing, slip casting, tape casting and other methods, and then placed in a mold for reaction sintering. This method has a complicated preparation process, which not only causes waste of materials and increases costs, but also cannot prepare devices with complex structures and micro devices with fine structures.

[0003] In recent years, additive manufacturing technology has developed rapidly and has received extensive attention and attention from researchers at home and abroad. Photocuring 3D printing is to focus lasers of specific wavelengths and intensities on the surface of photocurable materials, so that they are stacked layer by layer and cured to form a preset three-dimensional entity. This manufacturing technology effectively solves the problem of material waste, and can complete the molding of devices with complex shapes or fine structures under computer-aided work.

[0004] Ceramic slurry is both the key and the foundation of photocuring printing technology. First of all, ceramic slurry needs to have excellent stability and dispersibility. The liquid phase dispersion medium should fully wet the ceramic particles with high surface energy, and stabilize the dispersed phase such as primary particles through stabilizing effects such as electrostatic action or steric hindrance, so as to prevent collision agglomeration and gravity sedimentation due to Brownian motion. However, ceramic powders with high surface energy are difficult to disperse in organic phases with low surface energy. Therefore, the common ceramic slurries are prone to sedimentation, resulting in uneven prints. Secondly, increasing the solid content of the printing slurry has always been a problem. Simply increasing the proportion of ceramic powder will cause a sharp increase in the viscosity of the slurry, making it difficult to ensure leveling. Finally, printed ceramic parts need to go through a degreasing process to remove organic impurities and undergo sintering to achieve densification. Ceramic materials are usually prone to form carbide organic impurities residues when degreased in the air, and YAG ceramics are extremely sensitive to impurity content. Therefore, how to achieve effective degreasing and densification of ceramic prints has become a problem that needs to be solved urgently. Summary of the invention

[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0006] In order to achieve these purposes and other advantages of the present invention, a method for preparing a YAG ceramic slurry for photocuring molding is provided, comprising the following steps:

[0007] Step 1: Prepare surface-modified YAG powder. The specific method is as follows:

[0008] S11, mixing anhydrous ethanol and a modifier, stirring after ultrasonication, to obtain a modifier solution;

[0009] S12, adding YAG powder to the modifier solution, mixing by ball milling, and obtaining a mixture;

[0010] S13, drying the mixture obtained in S2, grinding and sieving to obtain surface-modified YAG powder;

[0011] Step 2: prepare a photocurable resin, add a photoinitiator and a dispersant thereto in sequence, and stir under light-proof conditions to obtain a photocurable resin system mixed solution;

[0012] Step 3: The surface-modified YAG powder and the mixed solution of the photocurable resin system are mixed and ball-milled to obtain a YAG ceramic slurry for photocuring molding.

[0013] Preferably, in step 1, the modifier is at least one of sebacic acid and glutaric acid; the concentration of the modifier solution is 0.1-1.0 wt%; ultrasonication is performed for 2-5 min, and stirring is performed for 0.5-1.5 h.

[0014] Preferably, in the step 1, the mass ratio of YAG powder to modifier solution is 1 to 3:1; the specific parameters of ball milling mixing are: rotation speed 200 to 400 r / min, clockwise ball milling for 20 minutes and stop for 15 minutes, then counterclockwise ball milling for 20 minutes and stop for 15 minutes, ball-to-material ratio 2 to 5:1, and ball milling for 6 to 10 hours.

[0015] Preferably, in the step 1, drying is performed at a constant temperature of 50-70° C. until the anhydrous ethanol is completely evaporated; and grinding is performed through a 300-500 mesh sieve.

[0016] Preferably, in the step 2, the photocurable resin is prepared by mixing 1,6-hexanediol diacrylate (HDDA), hydroxyethyl acrylate (HEA) and trimethylolpropane triacrylate (TMPTA) in a mass ratio of 5 to 7:2 to 4:1, and magnetically stirring for 2 to 4 hours under light-proof conditions to obtain the photocurable resin.

[0017] Preferably, in step 2, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and the amount used is 1 wt % of the mass of the photocurable resin.

[0018] Preferably, in step 2, the dispersant is at least one of KH550 and KOS110, and based on the mass of the surface-modified YAG powder in step 3, the added amount of the dispersant is 5 wt %.

[0019] Preferably, in the step 2, stirring is performed for 0.5 to 1.5 hours in a light-proof condition.

[0020] Preferably, in step three, the volume ratio of the surface modified YAG powder and the photocurable resin system mixed liquid is 40-50:50-60; the specific parameters of ball milling are: rotation speed 200-400 r / min, ball-to-material ratio 2-5:1, and ball milling time 3-7h.

[0021] Preferably, in step 1, the method for preparing the surface-modified YAG powder is replaced by:

[0022] S11, mixing anhydrous ethanol and sebacic acid, ultrasonicating for 2 to 5 minutes, and then magnetically stirring for 0.5 to 1.5 hours to prepare a sebacic acid solution with a mass fraction of 0.1 to 1.0 wt%;

[0023] S12, mixing anhydrous ethanol, polyethylene glycol-200 and KH550, ultrasonically treating for 2 to 5 minutes, magnetically stirring for 0.5 to 1.5 hours, adding acetic acid to adjust the pH to 4 to 6, and obtaining a second solution; wherein, in the second solution, the mass fraction of polyethylene glycol-200 is 0.1 to 0.5 wt%, and the mass fraction of KH550 is 0.1 to 0.5 wt%;

[0024] S13, according to the mass ratio of YAG powder to sebacic acid solution of 1 to 3:1, add YAG powder to sebacic acid solution, ball milling and mixing for 6 to 10 hours, add the obtained product to the second solution at a mass ratio of 1:1 to 2, place it between two copper electrodes, apply alternating current to the two copper electrodes, and use alternating electric field treatment for 20 to 60 minutes to obtain a second mixed solution; wherein, the specific parameters of ball milling are: ball-to-material ratio of 2 to 5:1, rotation speed of 200 to 400 r / min, first clockwise ball milling for 20 minutes and stopping for 15 minutes, then counterclockwise ball milling for every 20 minutes and stopping for 15 minutes, and so on; the specific parameters of the alternating electric field are: voltage amplitude of 50 to 200 V, frequency of 100 to 400 Hz, waveform of sawtooth wave or sine wave;

[0025] S14, drying the second mixed solution at a constant temperature of 50-70° C. until the anhydrous ethanol is completely evaporated, and grinding the mixed solution through a 300-500 mesh sieve to obtain a surface-modified YAG powder.

[0026] An application of the YAG ceramic slurry prepared by the preparation method as described above for photocuring molding, wherein the YAG ceramic slurry is used to prepare a YAG ceramic material with a preset structure by photocuring 3D printing, comprising the following steps:

[0027] S1. Place the YAG ceramic slurry for photocuring into a photocuring 3D printer, and print layer by layer according to the preset three-dimensional model. Each layer is formed by photocuring. The thickness of the single layer is 50 to 100 μm, and the curing time of the single layer is 5 to 15 seconds to obtain a printed body with a preset structure.

[0028] S2, after drying the printed body obtained in S1, put it into isopropanol for ultrasonic treatment for 3 to 8 minutes, then put it into anhydrous ethanol for ultrasonic treatment for 5 to 15 minutes, take it out and irradiate it under ultraviolet light for 10 to 14 hours to obtain a light-cured printed body;

[0029] S3, degreasing the printed body after light curing to obtain a degreased YAG ceramic body;

[0030] S4, sintering the degreased YAG ceramic body to obtain a YAG ceramic material.

[0031] Preferably, in S3, the specific method of degreasing is: placing the photocured printed body into a tubular furnace, heating it from room temperature to 150-250°C at a rate of 1-3°C / min under vacuum conditions and keeping it warm for 80-100 min, then heating it to 200-300°C and keeping it warm for 80-100 min, then heating it to 250-350°C and keeping it warm for 80-100 min, so that the organic matter in the body is fully pyrolyzed, and finally keeping it at 500-700°C for 100-200 min and then cooling it with the furnace to obtain a degreased YAG ceramic body.

[0032] Preferably, in S4, the specific method of sintering is: placing the degreased YAG ceramic body into a high-temperature sintering furnace, and placing a small amount of layered alumina at the bottom of the crucible to prevent the YAG ceramic body from sticking to the crucible at high temperature, heating from room temperature to 1300-1500°C at a rate of 5-15°C / min, keeping warm for 100-140min, heating to 1500-1700°C at a rate of 2-7°C / min, and then heating to 1600-1800°C at a rate of 1-3°C / min and keeping warm for 250-350min, so that the grains grow fully and the pores are discharged, thereby making the ceramic dense, and finally cooling to 1100-1300°C at a rate of 3-5°C / min, cooling to room temperature with the furnace after it stabilizes, and obtaining a YAG ceramic material.

[0033] The present invention has at least the following beneficial effects:

[0034] 1) The present invention prepares a light-cured ceramic slurry from yttrium aluminum garnet (YAG) ceramic powder by mechanical stirring and ball milling, providing a method for producing YAG ceramic materials on a large scale with a simple process. The slurry preparation process is simple, the stability is high, the solid content is high, the printed part solvent and the cross-linking agent are easy to remove, and the mechanical properties of the YAG ceramic material are effectively guaranteed;

[0035] 2) The YAG ceramic slurry prepared by the present invention has excellent performance and stable properties. Its viscosity can be achieved by adjusting the solid content and the proportion of additives within a certain range according to printing requirements, and has a wide range of applications;

[0036] 3) The present invention uses dicarboxylic acid to modify the surface of YAG ceramic powder, thereby improving the dispersibility and slurry stability of the YAG ceramic powder. By adjusting the proportions of different photocurable resins, photoinitiators, and dispersants, effective control of the slurry rheological properties can be achieved to meet the needs of photocuring molding under different conditions. The printed YAG ceramics can be degreased and sintered to achieve a relative density of 97.5%.

[0037] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a viscosity curve of the YAG ceramic slurry prepared in Example 1;

[0039] Figure 2 A comparison chart of the viscosity of the YAG ceramic slurry prepared in Example 2 and Comparative Example 1;

[0040] Figure 3 This is a relative density comparison diagram of the printed body after photocuring, the YAG ceramic body after degreasing, and the YAG ceramic material after sintering in Example 3;

[0041] Figure 4 is a viscosity curve of the YAG ceramic slurry prepared in Example 4;

[0042] Figure 5 This is a viscosity curve of the YAG ceramic slurry prepared in Example 5. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0044] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0045] Example 1

[0046] A method for preparing a YAG ceramic slurry for photocuring molding comprises the following steps:

[0047] Step 1: Preparation of surface modified YAG powder:

[0048] S11, adding anhydrous ethanol and glutaric acid into a beaker, ultrasonicating for 3 minutes and then magnetically stirring for 1 hour to prepare a glutaric acid solution with a mass fraction of 0.5 wt%;

[0049] S12, according to the mass ratio of YAG powder to glutaric acid solution of 2:1, adding YAG powder to glutaric acid solution, using a ball mill to mix for 8 hours to obtain a mixture; wherein the specific parameters of ball milling are: ball-to-material ratio of 3:1, rotation speed of 300r / min, first clockwise ball milling for 20 minutes and stopping for 15 minutes, then counterclockwise ball milling for every 20 minutes and stopping for 15 minutes, and so on;

[0050] S13, placing the mixture obtained in step S12 in an oven at a constant temperature of 60° C. to dry until the anhydrous ethanol is completely evaporated, and grinding through a 400-mesh sieve to obtain surface-modified YAG powder;

[0051] Step 2, preparing a photocurable resin: 1,6-hexanediol diacrylate, hydroxyethyl acrylate and trimethylolpropane triacrylate were mixed in a mass ratio of 6:3:1, and magnetically stirred for 3 hours under light-proof conditions to obtain a photocurable resin;

[0052] Step 3: Add photoinitiator TPO and dispersant KOS110 to the above-mentioned photocurable resin in sequence, and stir magnetically for 1 hour under light-proof conditions to obtain a photocurable resin system mixed liquid; wherein the photoinitiator is 1wt% of the mass of the photocurable resin, and the dispersant is 5wt% of the mass of the surface-modified YAG powder;

[0053] Step 4: Pour the surface modified YAG powder and the photocurable resin system mixture into a ball mill at a volume ratio of 45 vol%:55 vol%, and mix them in a ball mill at a ball-to-material ratio of 3:1 for 5 h at a rotation speed of 300 r / min to obtain a YAG ceramic slurry (viscosity <50 Pa·s) for photocuring molding. The viscosity curve is as follows: Figure 1 As shown in Figure 2, with the increase of shear rate, the viscosity of YAG ceramic slurry gradually decreases from 30.53 Pa·s to 1.43 Pa·s.

[0054] Example 2

[0055] In this embodiment, sebacic acid is used to replace glutaric acid, and the remaining steps are the same as those in Embodiment 1 to obtain a YAG ceramic slurry (viscosity <10 Pa·s) for photocuring.

[0056] Comparative Example 1

[0057] In this comparative example, YAG ceramic slurry was prepared using YAG powder without surface modification, and the remaining steps were the same as those in Example 1, including the following steps:

[0058] Step 1, preparing a photocurable resin: 1,6-hexanediol diacrylate, hydroxyethyl acrylate and trimethylolpropane triacrylate were mixed in a mass ratio of 6:3:1, and magnetically stirred for 3 hours under light-proof conditions to obtain a photocurable resin;

[0059] Step 2: Add photoinitiator TPO and dispersant KOS110 to the above-mentioned photocurable resin in sequence, and stir magnetically for 1 hour under light-proof conditions to obtain a photocurable resin system mixed liquid; wherein the photoinitiator is 1wt% of the mass of the photocurable resin, and the dispersant is 5wt% of the mass of the YAG powder;

[0060] Step 3: Weigh YAG powder and photocurable resin system mixed solution at a volume ratio of 45 vol%:55 vol% respectively and pour them into a ball mill. Mix them in a ball mill at a ball-to-material ratio of 3:1 for 5 hours at a rotation speed of 300 r / min to obtain YAG ceramic slurry (viscosity > 50 Pa·s) for photocuring molding.

[0061] Figure 2 2 is a viscosity curve of the YAG ceramic slurry prepared in Example 2 and Comparative Example 1. It can be seen that the YAG ceramic slurry prepared by using the YAG powder surface-modified with sebacic acid in Example 2 has a lower viscosity. With the increase of the shear rate, the viscosity of the YAG ceramic slurry prepared in Example 2 decreases from 6.57 Pa·s to 0.17 Pa·s, and the viscosity of the YAG ceramic slurry prepared in Comparative Example 1 decreases from 51.97 Pa·s to 2.99 Pa·s.

[0062] Example 3

[0063] An application of YAG ceramic slurry for photocuring molding comprises the following steps:

[0064] Step 1, the YAG ceramic slurry obtained in Example 1 is placed in a light-curing 3D printer with a wavelength of 430nm, and printing is performed according to the sliced ​​three-dimensional model. The structure of the first layer is formed by light curing, and the thickness of the single layer is 50μm. The single layer curing time is 10s. Then, the remaining slurry is covered on the first layer by the scraper of the printer, and the structure of the second layer is formed by light curing. After continuously repeating the above steps, the printed body is gradually formed to form a predetermined structure;

[0065] Step 2: After the printed body obtained in step 1 is dried, it is placed in isopropanol for ultrasonic treatment for 5 minutes, and then placed in anhydrous ethanol for ultrasonic treatment for 10 minutes, taken out and irradiated under ultraviolet light for 12 hours to obtain a photocured printed body with a relative density of 56.2%;

[0066] Step 3: Place the photocured printed body into a vacuum tube furnace for degreasing: evacuate and fill with inert gas, repeat three times to exclude air, then heat from room temperature to 200°C at a rate of 1°C / min under vacuum conditions for 90 minutes, then heat to 250°C for 90 minutes, then heat to 300°C for 90 minutes, so that the organic matter in the body is fully pyrolyzed, and finally heat to 600°C for 150 minutes and then cool with the furnace to obtain a degreased YAG ceramic body with a relative density of 80.3%;

[0067] Step 4: Place the degreased YAG ceramic body in step 3 into a high-temperature sintering furnace, and place a small amount of layered alumina at the bottom of the crucible to prevent the YAG ceramic body from sticking to the crucible at high temperature. Heat from room temperature to 1400°C at a heating rate of 10°C / min. After keeping warm for 120 minutes, heat to 1600°C at a rate of 5°C / min, and then heat to 1700°C at a rate of 2°C / min and keep warm for 300 minutes to allow the grains to grow fully and discharge the pores, thereby making the ceramic dense. Finally, cool to 1200°C at a rate of 4°C / min, and cool to room temperature with the furnace after it stabilizes to obtain a YAG ceramic material with a relative density of 97.5%.

[0068] Figure 3 This is a relative density comparison diagram of the YAG ceramic body after light curing, the YAG ceramic body after degreasing, and the YAG ceramic material after sintering in this embodiment.

[0069] Example 4

[0070] This embodiment provides a method for preparing a YAG ceramic slurry for photocuring molding. Only the preparation method of the surface-modified YAG powder is changed, and the remaining steps are the same as those in Embodiment 1. The preparation method of the surface-modified YAG powder is as follows:

[0071] S11, adding anhydrous ethanol and sebacic acid into a beaker, ultrasonicating for 3 minutes and then magnetically stirring for 1 hour to prepare a sebacic acid solution with a mass fraction of 0.5 wt%;

[0072] S12, adding anhydrous ethanol, polyethylene glycol-200 and KH550 to a beaker, ultrasonically treating for 3 minutes, magnetically stirring for 1 hour, adding acetic acid to adjust the pH to 6, and obtaining a second solution; wherein, in the second solution, the mass fraction of polyethylene glycol-200 is 0.3wt%, and the mass fraction of KH550 is 0.2wt%;

[0073] S13, according to the mass ratio of YAG powder to sebacic acid solution being 2:1, YAG powder is added to sebacic acid solution, mixed by ball mill for 8 hours, the obtained product is added to the second solution at a mass ratio of 1:1, placed between two copper electrodes, alternating current is applied to the two copper electrodes, and treated by alternating electric field for 30 minutes to obtain a second mixed solution; wherein, the specific parameters of ball milling are: ball-to-material ratio 3:1, rotation speed 300r / min, first clockwise ball milling for 20 minutes and stopping for 15 minutes, then counterclockwise ball milling for every 20 minutes and stopping for 15 minutes, and so on; the specific parameters of alternating electric field are: voltage amplitude is 100V, frequency is 200Hz, and waveform is sawtooth wave;

[0074] S14, placing the second mixed liquid in an oven at a constant temperature of 60° C. for drying until the anhydrous ethanol is completely evaporated, and grinding it through a 400-mesh sieve to obtain surface-modified YAG powder.

[0075] In this embodiment, sebacic acid, polyethylene glycol-200 and KH550 are respectively used as modifiers to modify the surface of YAG powder, which can reduce the surface energy of the powder, reduce the friction between particles, and provide greater steric hindrance. The mixed liquid is treated with an alternating electric field to improve the uniformity of the powder particle size, promote the coordination bonding between the modifier and the YAG powder, and cover the YAG powder more completely and evenly, promote surface modification, avoid collision and agglomeration between powders, improve its dispersibility, and further reduce the viscosity of the YAG ceramic slurry. At the same solid content, the viscosity of the YAG ceramic slurry prepared in Example 4 is lower than that in Examples 1 to 2. Figure 4 As shown, with the increase of shear rate, the viscosity of the YAG ceramic slurry prepared in Example 4 decreased from 5.02 Pa·s to 0.05 Pa·s.

[0076] Example 5

[0077] This embodiment provides a method for preparing a YAG ceramic slurry for photocuring. When preparing the surface-modified YAG powder, no alternating electric field treatment is used. The remaining steps are the same as those in Embodiment 4. The method for preparing the surface-modified YAG powder is as follows:

[0078] S11, adding anhydrous ethanol and sebacic acid into a beaker, ultrasonicating for 3 minutes and then magnetically stirring for 1 hour to prepare a sebacic acid solution with a mass fraction of 0.5 wt%;

[0079] S12, adding anhydrous ethanol, polyethylene glycol-200 and KH550 to a beaker, ultrasonically treating for 3 minutes, magnetically stirring for 1 hour, adding acetic acid to adjust the pH to 6, and obtaining a second solution; wherein, in the second solution, the mass fraction of polyethylene glycol-200 is 0.3wt%, and the mass fraction of KH550 is 0.2wt%;

[0080] S13, according to the mass ratio of YAG powder to sebacic acid solution of 2:1, YAG powder is added to the sebacic acid solution, and mixed by ball mill for 8 hours, and the obtained product is added to the second solution at a mass ratio of 1:1, and stirred for 30 minutes to obtain a second mixed solution; wherein, the specific parameters of ball milling are: ball-to-material ratio of 3:1, rotation speed of 300r / min, first clockwise ball milling for 20 minutes and stopping for 15 minutes, then counterclockwise ball milling for every 20 minutes and stopping for 15 minutes, and so on;

[0081] S14, placing the second mixed liquid in an oven at a constant temperature of 60° C. for drying until the anhydrous ethanol is completely evaporated, and grinding it through a 400-mesh sieve to obtain surface-modified YAG powder.

[0082] like Figure 5 As shown, with the increase of shear rate, the viscosity of the YAG ceramic slurry prepared in Example 5 decreased from 5.76 Pa·s to 0.12 Pa·s.

[0083] Example 6

[0084] The present embodiment provides a method for preparing a YAG ceramic slurry for photocuring molding, wherein the volume ratio of the surface-modified YAG powder and the photocurable resin system mixed liquid in step three is changed to 50 vol%:50 vol%, that is, the solid content is increased to 50 vol%, and the remaining steps are the same as those in embodiment 4, to obtain a YAG ceramic slurry for photocuring molding (viscosity <10 Pa·s).

[0085] Example 7

[0086] In this embodiment, the YAG ceramic slurry obtained in Example 6 is used for photocuring 3D printing, and the remaining steps are the same as those in Example 3 to obtain a YAG ceramic material with a relative density of 98.8%.

[0087] The solid content of the printing slurry will affect its printing performance, green body density and mechanical properties. Simply increasing the proportion of ceramic powder will lead to a sharp increase in the slurry viscosity, making it difficult to ensure the rheological properties. Increasing the solid content while maintaining the rheological properties of the slurry can reduce the proportion of organic matter, and in the subsequent degreasing and sintering process of the ceramic green body, problems such as cracking of the green body caused by pyrolysis and volatilization of organic matter can be avoided, thereby ensuring the density and mechanical properties of the ceramic green body. In Example 6, the solid content was increased to 50 vol%, and the prepared YAG ceramic slurry still had a low viscosity (<10 Pa·s) and could be used for photocuring 3D printing. The relative density of the YAG ceramic material obtained in Example 7 reached 98.8%.

[0088] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing YAG ceramic slurry for photocuring molding, characterized in that: The following steps are involved: Step 1: Prepare surface modified YAG powder. The specific method is as follows: S11, mixing anhydrous ethanol and a modifier, stirring after ultrasonication, to obtain a modifier solution; S12, adding YAG powder to the modifier solution, mixing by ball milling, and obtaining a mixture; S13, drying the mixture obtained in S12, grinding and sieving to obtain surface-modified YAG powder; Step 2: prepare a photocurable resin, add a photoinitiator and a dispersant thereto in sequence, and stir under light-proof conditions to obtain a photocurable resin system mixed solution; Step 3: The surface-modified YAG powder and the mixed solution of the photocurable resin system are mixed and ball-milled to obtain a YAG ceramic slurry for photocuring molding.

2. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 1, the modifier is at least one of sebacic acid and glutaric acid; the concentration of the modifier solution is 0.1-1.0 wt%; ultrasonication is performed for 2-5 minutes, and stirring is performed for 0.5-1.5 hours.

3. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 1, the mass ratio of YAG powder to modifier solution is 1-3:1; the specific parameters of ball milling mixing are: rotation speed 200-400 r / min, clockwise ball milling for 20 minutes and stop for 15 minutes, then counterclockwise ball milling for 20 minutes and stop for 15 minutes, ball-to-material ratio 2-5:1, and ball milling for 6-10 hours.

4. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 1, drying is performed at a constant temperature of 50-70° C. until the anhydrous ethanol is completely evaporated; and grinding is performed through a 300-500 mesh screen.

5. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 2, the photocurable resin is prepared by mixing 1,6-hexanediol diacrylate, hydroxyethyl acrylate and trimethylolpropane triacrylate in a mass ratio of 5-7:2-4:1, and magnetically stirring for 2-4 hours in a light-proof condition to obtain the photocurable resin.

6. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 2, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the amount used is 1wt% of the mass of the photocurable resin; the dispersant is at least one of KH550 and KOS110, and the amount used is 5wt% of the mass of the surface modified YAG powder; stirring is carried out for 0.5 to 1.5 hours under light-proof conditions.

7. The method for preparing a YAG ceramic slurry for photocuring molding according to claim 1, characterized in that: In the step 3, the volume ratio of the surface modified YAG powder and the light-curable resin system mixed liquid is 40-50:50-60; the specific parameters of the ball milling are: rotation speed 200-400 r / min, ball-to-material ratio 2-5:1, and ball milling 3-7 hours.

8. An application of the YAG ceramic slurry for photocuring prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The YAG ceramic slurry is used to prepare a YAG ceramic material with a preset structure by photocuring 3D printing, comprising the following steps: S1. Place the YAG ceramic slurry for photocuring into a photocuring 3D printer, and print layer by layer according to a preset three-dimensional model, with a single layer thickness of 50 to 100 μm and a single layer curing time of 5 to 15 seconds to obtain a printed body with a preset structure; S2, after drying the printed body obtained in S1, put it into isopropanol for ultrasonic treatment for 3 to 8 minutes, then put it into anhydrous ethanol for ultrasonic treatment for 5 to 15 minutes, take it out and irradiate it under ultraviolet light for 10 to 14 hours to obtain a light-cured printed body; S3, degreasing the printed body after light curing to obtain a degreased YAG ceramic body; S4, sintering the degreased YAG ceramic body to obtain a YAG ceramic material.

9. The use of the YAG ceramic slurry for photocuring molding according to claim 8, characterized in that: In the S3, the specific method of degreasing is: placing the photocured printed body into a tubular furnace, heating it from room temperature to 150-250°C at a rate of 1-3°C / min under vacuum conditions and keeping it warm for 80-100 min, then heating it to 200-300°C and keeping it warm for 80-100 min, then heating it to 250-350°C and keeping it warm for 80-100 min, and finally keeping it warm at 500-700°C for 100-200 min and then cooling it with the furnace to obtain a degreased YAG ceramic body.

10. The use of the YAG ceramic slurry for photocuring molding according to claim 8, characterized in that: In the S4, the specific sintering method is: putting the degreased YAG ceramic body into a high-temperature sintering furnace, and placing a small amount of layered alumina at the bottom of the crucible to prevent the YAG ceramic body from sticking to the crucible at high temperature, heating from room temperature to 1300-1500°C at a rate of 5-15°C / min, keeping warm for 100-140min, heating to 1500-1700°C at a rate of 2-7°C / min, then heating to 1600-1800°C at a rate of 1-3°C / min and keeping warm for 250-350min, and finally cooling to 1100-1300°C at a rate of 3-5°C / min, cooling to room temperature with the furnace, and obtaining a YAG ceramic material.

Citation Information

Patent Citations

  • Yttria-stabilized zirconia powder, method for preparing same and ceramic

    CN108439978A

  • Method for preparing YAG transparent ceramics based on improved Isobam gel system

    CN108516818A

  • Ceramic material for 3D light curing formation printing and preparation method of ceramic element

    CN109400177A

  • Preparation method for photocured 3D-printed spiral type ceramic spring

    CN109867527A

  • DLP surface exposure molding technology based preparation method for bioactive porous ceramics

    CN110092652A